Economic Education Literature in the Context of Development: The Interconnection between the Economy and Education - Hendra, Muhammad; Judijanto, Loso; Fauzi, Muhammad Sukron (The Future of Education Journal, 2025)
This study aims to explore the literature on economic education in the context of economic development and its connection to a nation's growth. Economic education not only focuses on understanding basic economic concepts but also serves as an investment in developing skilled and productive human resources. Based on the analysis of economic theories such as the human capital theory (Schultz, 1961) and endogenous growth theory (Romer, 1990), this study finds that economic education has a significant impact on improving workforce quality, fostering innovation, and enhancing a country's economic competitiveness. Moreover, economic education can help reduce socio-economic disparities by providing broader access to the knowledge and skills needed in the global economy. Thus, economic education plays a crucial role in promoting sustainable and inclusive economic development. The findings of this study indicate that the development of a relevant and high-quality economic education system is essential to prepare human resources capable of facing future challenges and contributing to long-term economic growth.